Game-Based Learning Model with A Culturally Responsive Teaching Approach to Enhance Student’ Motivation in Learning Mathematics - Jasmaniah Jasmaniah; Nurhayati Nurhayati; Fatma Zuhra (Universitas Pendidikan Ganesha, 2024)
Most students still tend to assume that mathematics is a difficult subject to understand, and the lecture method still dominates the way teachers teach. To overcome this problem, one solution to increase student motivation is to use the Game-Based Learning (GBL) model with the Culturally Responsive Teaching (CRT) approach. Combining the two can create a more effective and relevant learning model for students from diverse backgrounds. The study aims to analyze the increase in student learning motivation through the implementation of the CRT integrated GBL learning model. This research method is quasi-experimental with a one-group pretest-posttest design. Before and after learning, a motivation questionnaire with 20 statements was distributed to 19 students to measure their learning motivation. Learning took place over two meetings, during which students were actively involved in activities that introduced concepts gradually until they achieved the learning objectives. The data collected were then analyzed using the gain index (N-Gain) to assess the increase in motivation. The results of the study showed that the CRT-integrated GBL learning model is effective in increasing students' learning motivation because this approach not only offers games but also designs activities that guide students in gradually understanding concepts and achieving learning objectives.